ANALISIS DANA PIHAK KETIGA (DPK) DAN PEMBIAYAAN TERHADAP TOTAL ASET PADA BANK SYARIAH INDONESIA TAHUN 2022-2024 - Rully Trihantana; Tubagus Rifqy Thantawi; Puloh; Marini Ayu Saputriansyah (JURNAL KAJIAN ISLAM MODERN, 2026)
Total assets are an indicator that can assess the performance and growth of Islamic banking. Several factors that cause total asset growth are due to the bank's ability to collect Third Party Funds and how much the bank can optimally distribute financing. This study aims to analyze the effect of Third Party Funds and Financing on Total Assets at Indonesian Islamic Banks in 2022-2024. This approach uses a quantitative descriptive method. The type of data used is secondary data derived from the quarterly reports of Indonesian Islamic Banks in 2022-2024. The results of this study indicate that Third Party Funds (X1) partially influence Total Assets (Y) with a significance value of (0.000) < α (0.05) and a calculated t value (5.544) > t table (2.626). Therefore, H0 is rejected and H1 is accepted. Meanwhile, Financing (X1) partially influences Total Assets (Y), with a significance value of 0.003 < α (0.05) and a calculated t- value of 4.119 > t-table (2.626). Therefore, H0 is rejected and H1 is accepted. Third Party Funds (X1) and Financing (X2) simultaneously influence Total Assets (Y), with a significance value of 0.000 < α (0.05) and a calculated t-value of 443.518 > t-table (4.46). Therefore, H0 is rejected and H1 is accepted.